2019
DOI: 10.2147/idr.s225288
|View full text |Cite
|
Sign up to set email alerts
|

<p>PAU-1, a Novel Plasmid-Encoded Ambler Class A β-Lactamase Identified in a Clinical <em>Pseudomonas aeruginosa</em> Isolate</p>

Abstract: PurposeThe aim of this work was to identify a novel β-lactamase gene blaPAU-1 encoded on the plasmid of a clinical Pseudomonas aeruginosa isolate.Materials and methodsThe clinical P. aeruginosa isolates were isolated from a hospital in southern China. Molecular cloning was performed to analyze the function of the resistance gene. The minimum inhibitory concentration (MIC) was determined by means of the agar dilution method to determine the antimicrobial susceptibilities of the strains. Whole-genome sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Analysis of the adjacent genetic elements of bla CAE-1 in p1_SCLZS63 and the above four bla CAE-1 -carrying sequences showed that bla CAE-1 is always reversely located at the immediate upstream of the LysR family transcriptional activator-encoding gene ampR (Fig. 2 ), which consists with the commonly seen lysR -accompanied class A β-lactamases as described previously 36 . In all sequences except pB1A, the bla CAE-1 - ampR element is bounded by an intact IS caq2 (upstream of bla CAE-1 ) and a ΔIS caq2 (immediately downstream of bla CAE-1 ) that is truncated by a parallel IS caq1 (Fig.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Analysis of the adjacent genetic elements of bla CAE-1 in p1_SCLZS63 and the above four bla CAE-1 -carrying sequences showed that bla CAE-1 is always reversely located at the immediate upstream of the LysR family transcriptional activator-encoding gene ampR (Fig. 2 ), which consists with the commonly seen lysR -accompanied class A β-lactamases as described previously 36 . In all sequences except pB1A, the bla CAE-1 - ampR element is bounded by an intact IS caq2 (upstream of bla CAE-1 ) and a ΔIS caq2 (immediately downstream of bla CAE-1 ) that is truncated by a parallel IS caq1 (Fig.…”
Section: Resultssupporting
confidence: 64%
“…The novel class A β-lactamase is most closely related to CzoA-1 35 (Accession no. EFI60385), with only 52.7% amino acid identity, followed by PAU-1 36 (48.8%, APC57487), and AXC-1 (48.3%, ATG32091) (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…(46). In a prior study, it was discovered that a clinical isolate of Pseudomonas aeruginosa contained a transferable plasmid containing the gene known as blaPAU-1, which is connected to the mobile genetic element (47). Considering the high ubiquity of beta-lactam resistance genes, it is preferable to monitor the level of antibiotic resistance and resistance genes in patients with Pseudomonas aeruginosa infection (48).…”
Section: The Description and Significant Observations Of Each Selecte...mentioning
confidence: 99%